Novel cytokine–antibody fusion protein, N-820, to enhance the functions of ex vivo expanded natural killer cells against Burkitt lymphoma. Issue 2 (27th October 2020) - Chu, Yaya; Nayyar, Gaurav; Kham Su, Nang; Rosenblum, Jeremy M; Soon-Shiong, Patrick; Lee, John; Safrit, Jeffrey T; Barth, Matthew; Lee, Dean; Cairo, Mitchell S
Abstract : Background: The prognosis of patients with relapsed or progressive B cell (CD20 + ) non-Hodgkin's lymphoma (B-NHL), including Burkitt lymphoma (BL), is dismal due to chemoradiotherapy resistance. Novel therapeutic strategies are urgently needed. N-820 is a fusion protein of N-803 (formerly known as ALT-803) to four single-chains of rituximab. This agent has tri-specific binding activity to CD20 and enhanced antibody-dependent cell-mediated cytotoxicity. Methods: We investigated the anti-tumor combinatorial effects of N-820 with ex vivo expanded peripheral blood natural killer (exPBNK) cells against rituximab-sensitive and rituximab-resistant CD20 + BL in vitro using cytoxicity assays and in vivo using human BL xenografted NOD/SCID/IL2rγnull (NSG) mice. We also investigated the cytokines/chemokines/growth factors released using ELISA and multiplex assay. Gene expression changes were examined using real-time PCR arrays. Results: N-820 significantly enhanced the expression of NK activating receptors (p<0.001) and the proliferation of exPBNK cells with enhanced Ki67 expression and Stat5 phosphorylation (p<0.001). N-820 significantly enhanced the secretion of cytokines, chemokines, and growth factors including GM-CSF, RANTES, MIP-1B (p<0.001) from exPBNK cells as compared with the combination of rituximab+N-803. Importantly, N-820 significantly enhanced in vitro cytotoxicity (p<0.001) of exPBNK with enhanced granzyme B and IFN-γ release (p<0.001) against BL. Gene expression profiles in exPBNK stimulated by N-820+Raji-2R showed enhanced transcription of CXCL9, CXCL1, CSF2, CSF3, GZMB, and IFNG . Moreover, N-820 combined with exPBNK significantly inhibited rituximab-resistant BL growth (p<0.05) and extended the survival (p<0.05) of BL xenografted NSG mice. Conclusions: Our results provide the rationale for the development of a clinical trial of N-820 alone or in combination with endogenous or ex vivo expanded NK cells in patients with CD20 + B-NHL failing prior rituximab containing chemoimmunotherapy regimens.